Circular RNA CDR1as/ciRS-7– a novel biomarker in solid tumors - Zhang, Yun; Xiong, Chanyu; Jiang, Zhilin; Wang, Xiao; Ji, Juanjuan; Pan, Yan; Yu, Tianshu; Wang, Zihao; Zhu, Lin; Yue, Yumei; Li, Qiong; Wang, Haizhen; et al. (Frontiers in Oncology, 2024)
IntroductionCircular RNA CDR1as/ciRS-7 has been reported to function as an oncogenic regulator in various cancers. However, the prognostic value of CDR1as/ciRS-7 expression in solid tumors remains unclear. Herein, we conducted an updated meta-analysis to investigate the association between CDR1as/ciRS-7 expression and clinical outcomes in solid tumors.MethodsA systematic search was performed through the PubMed, EMBASE, Web of Science, and Ovid databases for eligible studies on clinical values of CDR1as/ciRS-7 in solid tumors. The pooled hazard ratios (HRs) or odd ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate the correlation between CDR1as/ciRS-7 and clinical outcomes.ResultsA total of 2424 patients from 17 studies between 2017 and 2023 were included. The results suggested that elevated CDR1as/ciRS-7 expression predicted a poor overall survival (OS) for 12 types of solid tumors (HR=1.93, 95% CI: 1.43-2.60, P<0.001) with no heterogeneity (I2 = 80.2%, P<0.001). Stratified analysis indicated that there was a negative relationship between CDR1as/ciRS-7 expression and OS in digestive system cancers (HR=2.30, 95% CI: 1.84-2.88, P<0.001), and respiratory cancers (HR=2.40, 95% CI: 1.75-3.30, P<0.001). Furthermore, we also revealed that CDR1as/ciRS-7 was positively related to tumor size (OR=2.11, 95%CI: 1.64-2.71, P<0.001), TNM stage (OR=2.05, 95%CI: 1.65-2.54, P<0.001), lymph node metastasis (LNM) (OR=1.74, 95%CI: 1.38-2.21, P<0.001), and distant metastasis (OR=2.79, 95%CI: 1.71-4.55, P<0.001). Although the probable evidence of publication bias was found in the studies with OS, tumor size, TNM stage, and LNM, the trim and fill analysis confirmed the reliability of these results was not affected.ConclusionElevated CDR1as/ciRS-7 expression was associated with larger tumor size, advanced TNM stage, worse LNM, distant metastasis, and shorter OS, suggesting that CDR1as/ciRS-7 may act as an independent prognostic biomarker in solid tumors.